O15 Primary HIV infection: lack of knowledge among men who have sex with men (MSM). (23rd May 2012) - Conway, K; Jack, D; Dew, C; Johnson, S; Cooper, V; Waters, L; Fisher, M
Abstract : Introduction: Primary HIV infection (PHI) is commonly symptomatic, offers an opportunity for early diagnosis and is important for individual health and preventing transmission. At risk populations should be aware of PHI symptoms. Aim: To ascertain PHI knowledge among UK MSM. Methods: Online anonymous survey conducted by the National AIDS Trust using the GaydarTM website between 31 March 2011 and 6 April 2011. Questions were asked about likelihood/nature of PHI symptoms and transmission risk. Data on recent HIV testing, HIV status and response to symptoms was collected. Analysis was done using χ 2 tests. Results: 8561 men responded: 76% had tested for HIV (16% positive), 21% were untested and 3% did not disclose. 5159/8548 (60%) believed PHI to be asymptomatic and 799/8548 (9%) correctly answered that 70%–90% would have symptoms; HIV+ MSM were significantly more likely to be aware of this than HIV-/untested MSM (14.9% vs 8.2%, p<0.0001) and MSM who had tested were more likely to be aware than never testers (10.2% vs 5.8%, p<0.0001). 2926/8267 (35.4%) identified the fever/sore throat/rash triad as the most common presentation of PHI. MSM who had never HIV tested were less likely to correctly identify these symptoms than those who had (29.3% vs 37.0%, p<0.0001). 2964/8450 (35.1%) believed it is hard to transmit HIV in early infection; the remainder recognised PHI as highly infectious. HIV+ MSM were more likely to recognise this than HIV-/untested MSM (76.8% vs 62.5%, p<0.0001) and untested MSM were less likely to recognise this than those who had tested (60.4% vs 66%, p<0.0001). 4220/6918 (61%) of HIV-/untested MSM would seek medical advice if symptomatic; the remainder would ignore symptoms or await resolution. Of those who would seek advice 54.1% would attend GP/NHS walk-in centre and 34.6% would attend GU clinic or take community HIV test. Discussion: This survey illustrates a concerning lack of knowledge among MSM regarding PHI symptoms and the urgent need for ongoing health promotion and education.